THE EFFECT OF BOARD DIVERSITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN INDONESIAN MANUFACTURING COMPANIES - Fina Tri Lestari; Muhamad Wahyudi; Nibras Anny Khabibah (Universitas Tidar, 2023)
This study aims to examine the disclosure of corporate social responsibility in manufacturing companies in Indonesia as influenced by the diversity of the company's board of directors and board of commissioners. A total of 142 manufacturing companies listed on the IDX from 2017- 2021 became the population of this study. Purposive sampling was used in sample selection, resulting in a research sample of 42 companies. During the 5 (five) years of observation, 210 observations were obtained. The results showed that gender diversity characterized by the presence of women on the company's board had a negative effect on corporate social responsibility disclosure, age diversity characterized by the presence of a young board on the company's board had no effect on corporate social responsibility disclosure, and the diversity of the company's board education background with management and business education had a positive effect on corporate social responsibility disclosure.